THE EFFECTIVENESS OF SNAKES AND LADDERS GAME TO IMPROVE STUDENTS’ MASTERY OF SIMPLE PAST TENSE IN CONSTRUCTING RECOUNT TEXTS (A Quasi-Experimental Research of the Eighth Grade Students of SMP N 2 Demak in the Academic Year of 2013/2014) (ELT Forum: Journal of English Language Teaching, 2014)
This study concerns with the use of snakes and ladders game as a medium to improve students’ mastery of simple past tense in constructing recount texts. The purposes of this study are to show whether snakes and ladders game gives contribution to improve the students’ mastery of simple past tense in constructing recount texts and to find out whether snakes and ladders game gives the significant difference or not. Quasi-experimental research was used. The population of this study was the eighth grade students of SMP N 2 Demak. The experimental group consisted of 30 students and the control group also consisted of 30 students. There were four meetings during the experiment. Before the experiment was conducted, a pre-test was given to both groups. A post-test was given after the experiment was done. To find out the significant difference statistically, t-test formula was used. Before applying the formula, the data were checked by using normality and homogeneity. The result shows that the data have normal distribution and homogeneity. The result of t-test is 3.41, for α = 5% with df = 58, t-table = 2.002. It means that the t-value is higher than the t-table (3.41 > 2.002). The purposes of this study are achieved because the students’ mastery of simple past tense in constructing recount texts improve. Then, the t-value of the post test is higher than the t-table; it means that the use of snakes and ladders gives the significant difference. In fact, based on this study the use of snakes and ladders game is effective and applicable enough as a teaching medium to be used in improving the students’ mastery of simple past tense in constructing recount texts.